Electronic Information and Publications: looking to the electronic future, let's not forget the archival past. Proceedings of the 24th annual Conference of the International Association of Aquatic and Marine Science Libraries and Information Centers (IAMSLIC) and the 17th Polar LIbraries Colloquy (PLC) ... : PLC Proceedings 17 ... - Markham, James W; Duda, Andrea L; Andrews, Martha (University of Alberta Library, 1998)
Proceedings of the joint Polar Libraries Colloquy and International Association of Aquatic and Marine Science Libraries and Information Centers Annual Conference held September 20 - 25, 1998 in Reykjavik, Iceland. ...